2001
DOI: 10.1097/00043426-200105000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma and Undifferentiated Sarcoma in the First Two Decades of Life: A Selective Review of Intergroup Rhabdomyosarcoma Study Group Experience and Rationale for Intergroup Rhabdomyosarcoma Study V

Abstract: Better understanding of biologic differences and new, active agents are needed to improve outcome of patients with unfavorable features at presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
215
1
15

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(252 citation statements)
references
References 27 publications
9
215
1
15
Order By: Relevance
“…The first IRSG study reported a 55% 5-year OS, which increased to 63% in the IRS-II study [2]. Similarly, the first SIOP study described a 52% OS (EFS 47%) [3].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The first IRSG study reported a 55% 5-year OS, which increased to 63% in the IRS-II study [2]. Similarly, the first SIOP study described a 52% OS (EFS 47%) [3].…”
Section: Discussionmentioning
confidence: 96%
“…This has been mainly due to the adoption of well-designed protocols based on a multidisciplinary approach. The first Italian protocol was designed on the strength of the initial IRSG experience [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 There are o20 prostatic rhabdomyosarcomas that have been reported in adults ranging in age from 17 to 68 years old. 20,21 As in younger patients, embryonal subtype is the predominant pattern.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%